Reflective Interaction as a paradigm intersecting creativity, musical education and music therapy (Orfeu, 2017)
The scope of this study is to present the "reflexive interaction" paradigm, created in the context of studies about human and machine interaction, and used within the scope of the MIROR Project - Musical Interaction Relying On Reflection.  In this project, a musical technology program was created  for children, which included improvising and creative body movement  activities, , applying the reflexive interaction paradigm in the field of musical creativity and in the field of children's motor creativity. The focus of this text is to highlight the reflexive interaction paradigm at the intersection between music education and music therapy as an effective theoretical framework to strengthen traits common to both areas, both from the point of view of theoretical application and practical experience.
Keywords: Reflexive Interaction; MIROR Project; Music Therapy; Music Education; Children